Impact de l’immigration, conséquences pour les immigrants : nouveaux résultats utilisant des données d’entreprises et sociales - Piché, Victor (Cahiers québécois de démographie)

(untitled) (Association des démographes du Québec, 2019)
For some time, many researchers have argued that the success of the next generation of research on the performance of immigrants in the labour market would be largely dependent on developing new databases. The conference organised by the CIQSS in October 2018 defined as its objective an examination of how far new databases are assisting in producing new research results and advancing the discussion of immigrants’ performance in the labour market as well as of the economic impact of immigration. This research note examines the contributions to this conference and concludes that, thanks partly to recent longitudinal databases, new research does offer innovative findings on both the factors involved in integration and also the economic effects of immigration.